College Student’s Culture from Mappi As A Source of Elementary School for Social Science Learning Based on Local Wisdom - Faisal Adenan; Andreas Erwin Prasetya; Pratiwi Pujiastuti (STAI Hubbulwathan Duri, 2022)
The research aims to describe the local wisdom possessed by college students and analyze the college student's local wisdom system with elementary social studies learning based on local wisdom. This study uses a qualitative approach with the research subjects of Class E students in the second semester of the 2020/2021 academic year, PGSD Study Program, Sanata Dharma University, Yogyakarta. The study found that there was a system of local wisdom that was still attached to the lives of Mappi Regency and can be integrated with elementary social studies learning. Elements of local wisdom that are part of students and have taken root into a cultural system include elements of language, technology systems/equipment/living equipment/, economic systems/livelihoods/, industry, social/community/organizational systems, religious systems, art systems and systems knowledge. The findings of the value of local wisdom inherent in students can be integrated and have implications for elementary social studies learning. Elementary Social Studies based on local wisdom is very important to foster students' love for local wisdom and as an effort to maintain the existence of local wisdom in the midst of the swift currents of globalization.